Local Prosecutors’ Response to Terrorism (2005) - M. Elaine Nugent, James L. Johnson, Brad Bartholomew, Delene Bromirski (My University, 2016)
The goal of the study is to ensure that prosecutors have the most current information about the enforcement of anti-terrorism statutes in order to ensure that the local efforts complement and not conflict with federal efforts. (palabras claves: ministerio público, terrorismo)